2011
DOI: 10.1063/1.3663332
|View full text |Cite
|
Sign up to set email alerts
|

How does spallation microdamage nucleate in bulk amorphous alloys under shock loading?

Abstract: Transmission electron microscopy of the amorphization of copper indium diselenide by in situ ion irradiation J. Appl. Phys. 111, 053510 (2012) Diffusion-controlled formation mechanism of dual-phase structure during Al induced crystallization of SiGe Appl. Phys. Lett. 100, 071908 (2012) Local structure of nitrogen in N-doped amorphous and crystalline GeTe Appl. Phys. Lett. 100, 061910 (2012) Facile creation of bio-inspired superhydrophobic Ce-based metallic glass surfaces Appl. Phys. Lett. 99, 261905 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 51 publications
0
25
1
1
Order By: Relevance
“…Just before void nucleation, the density begins to decrease a lot at the nucleation site. As free volume is believed to play an important role during the void nucleation process [46,49], this phenomenon is beyond our expectation. It implies that not only the free volume content but also the atomic packing has significant influence.…”
Section: Resultscontrasting
confidence: 38%
“…Just before void nucleation, the density begins to decrease a lot at the nucleation site. As free volume is believed to play an important role during the void nucleation process [46,49], this phenomenon is beyond our expectation. It implies that not only the free volume content but also the atomic packing has significant influence.…”
Section: Resultscontrasting
confidence: 38%
“…This results in the emergence of 10-nm-scaled shear bands, which macroscopically leads to shear-dominated failure [14,15]. However, recent experiments [14,[16][17][18] and simulations [1,3] have revealed that the dilatation itself, whether induced by shear or hydrostatic tension, can dominate the brittle failure of metallic glasses. In this case, the crack tip propagates via cavitation events that involve a series of nanoscale void nucleation and coalescence processes with very limited plastic growth.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the void nucleation mechanism, we proposed a we propose a void nucleation model of amorphous alloys developed from traditional stress temperature-driven models widely used in polycrystalline materials [6]. We also consider free-volume theory to understand and characterize microvoid nucleation in BMGs.…”
Section: Void Nucleation Mechanismmentioning
confidence: 99%